2020
DOI: 10.1108/ilt-03-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of operating conditions on cavitation induction of spiral groove liquid-film seal (SG-LFS)

Abstract: Purpose The purpose of this paper is to study the effects of operating conditions including process coefficient, lubricant viscosity and cavitation pressure on the cavitation of spiral groove liquid-film seal (SG-LFS). Design/methodology/approach A mathematical model of SG-LFS is established based on the JFO boundary and a relative de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Suzuki et al (2018) and Itadani et al (2020) found that cavitation plays a positive role in improving the pumping capacity and reducing leakage. Li et al (2020) investigated the cavitation of spiral groove liquid film seals based on the theory and experiment, focusing on the effects of operational and groove structure parameters. Letalleur et al (2002) used a flow factor model which provides an average description of the surface’s roughness impact and studied the effect of lubricant film flow between the two parallel sinusoidal wavy surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al (2018) and Itadani et al (2020) found that cavitation plays a positive role in improving the pumping capacity and reducing leakage. Li et al (2020) investigated the cavitation of spiral groove liquid film seals based on the theory and experiment, focusing on the effects of operational and groove structure parameters. Letalleur et al (2002) used a flow factor model which provides an average description of the surface’s roughness impact and studied the effect of lubricant film flow between the two parallel sinusoidal wavy surfaces.…”
Section: Introductionmentioning
confidence: 99%